2005
DOI: 10.1088/0022-3727/39/1/004
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the switching field and the intrinsic defects in near-stoichiometric lithium niobate crystals

Abstract: Several near-stoichiometric lithium niobate (LiNbO3) plates were prepared by the vapour transport equilibrium technique. Domain reversal was carried out on these samples by electric field poling. A nonlinear dependence of switching field on the concentration of anti-site niobium ( ) ions was observed. This nonlinear relationship was explained by a two-dimensional model based on the dynamics of the domain wall. A parameter of θc, denoting the critical position of the domain wall round ions, was introduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…51 Symmetric profiles are noted for the Hamiltonian breathers with the above input data wherein time-periodic breathers are clearly observed. 51 Symmetric profiles are noted for the Hamiltonian breathers with the above input data wherein time-periodic breathers are clearly observed.…”
Section: A Case Imentioning
confidence: 92%
“…51 Symmetric profiles are noted for the Hamiltonian breathers with the above input data wherein time-periodic breathers are clearly observed. 51 Symmetric profiles are noted for the Hamiltonian breathers with the above input data wherein time-periodic breathers are clearly observed.…”
Section: A Case Imentioning
confidence: 92%
“…This result is in agreement with the experimental observations of Yan et al, where they observed that the coercive field decreases with increasing Li content. 7 In order to facilitate the choice of MgLN crystal for lowest value of coercive field, one needs to optimize the Li/Nb ratio as well as Mg doping level. Figure 3 shows the dependence of coercive field on both the parameters.…”
Section: Resultsmentioning
confidence: 99%
“…3 that is based on literature data. [11][12][13][14] One sees that the coercive field strongly increases with decreasing lithium concentration, and the rate of this increase can be evaluated as ജ10 kV/ mm per 1 mol %. The UV-induced depletion of lithium can lead to a strong increase in E c and, consequently, to poling inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of E c is sensitive to the composition of the crystal. [11][12][13][14] In particular, it was found that the coercive field in nearly stoichiometric lithium niobate ͑SLN͒ crystals is roughly one order of magnitude smaller compared to that in the usual congruent lithium niobate ͑CLN͒, which is characterized by a Li deficiency of about 4 mol %. The Li content has therefore a strong impact on the value of E c .…”
Section: Introductionmentioning
confidence: 99%